Monolithically Programmed Stretchable Conductor by Laser‐Induced Entanglement of Liquid Metal and Metallic Nanowire Backbone. Issue 37 (28th July 2022) - Cho, Chulmin; Shin, Wooseop; Kim, Minwoo; Bang, Junhyuk; Won, Phillip; Hong, Sukjoon; Ko, Seung Hwan
Abstract: Owing to its low mechanical compliance, liquid metal is intrinsically suitable for stretchable electronics and future wearable devices. However, its invariable strain‐resistance behavior according to the strain‐induced geometrical deformation and the difficulty of circuit patterning limit the extensive use of liquid metal, especially for strain‐insensitive wiring purposes. To overcome these limitations, herein, novel liquid‐metal‐based electrodes of fragmented eutectic gallium‐indium alloy (EGaIn) and Ag nanowire (NW) backbone of which their entanglement is controlled by the laser‐induced photothermal reaction to enable immediate and direct patterning of the stretchable electrode with spatially programmed strain‐resistance characteristics are developed. The coexistence of fragmented EGaIn and AgNW backbone, that is, a biphasic metallic composite (BMC), primarily supports the uniform and durable formation of target layers on stretchable substrates. The laser‐induced photothermal reaction not only promotes the adhesion between the BMC layer and substrates but also alters the structure of laser‐irradiated BMC. By controlling the degree of entanglement between fragmented EGaIn and AgNW, the initial conductivity and local gauge factor are regulated and the electrode becomes effectively insensitive to applied strain. As the configuration developed in this study is compatible with both regimes of electrodes, it can open new routes for the rapid creation of complex stretchable circuitry through a single process. Abstract : A laser‐irradiated biphasic metallic composite (LIBMC) conductor, which has programmable and stretchable electromechanical properties, is developed. LIBMC gains unique characteristics such as varying conductivity from the features of the two nanomaterials, metal nanowire, and liquid metal, through a laser‐based facile fabrication process. This study indicates the possibility of the facile fabrication of complex stretchable electronics at the device level.